Pengukuran Kinerja Rantai Pasok Konstruksi Berkelanjutan dengan Pendekatan Model Supply Chain Operations Reference (SCOR) 12.0 - Moh Nur Sholeh; Mochamad Agung Wibowo; Undayani Cita Sari (Program Pendidikan Vokasi Universitas Indonesia, 2020)
The challenge of construction supply chain management is to maintain supply and demand in the supply chain flow and ensure a sustainable supply chain in the framework of lean construction. This challenge must be captured as part of the solution of the development of the rapidly growing construction industry. At present a sustainableSCOR on the Supply Chain Operations Reference (SCOR) version 12.0 has been developed. SustainableSCOR is a concept of a sustainable supply chain performance measurement approach by considering environmental aspects. The aim of this study is to adopt a supply chain performance measurement model in the sustainable construction of SCOR 12.0. The research method adopts standards, categories, and matrices in sustainableSCOR to a constructionally validated definition to academics and practitioners. The discussion of the supply chain continues with the calculation of each matrix. The results showed that all sustainableSCOR categories, namely materials, recycled inputs, recovered inputs, energy, water, emissions, and waste can be adopted to measure sustainable supply chain performance in construction. The adoption of this performance measurement needs to be detailed into one of the construction materials, in this study is steel material.